EVALUASI BANGUNAN DENGAN DETAILING DAN TANPA DETAILING MENGGUNAKAN PUSHOVER ANALYSIS BERDASARKAN ASCE 41-17 - Annisaa Yumna Aulia; Fritz Ferlin Kwannandar; Niar Resi Pramesthi (Racic : Rab Construction Research, 2025)
Indonesia is an earthquake-prone region, but many buildings are damaged when earthquakes occur, especially in non-engineered buildings, one of them is school buildings. School buildings in some cities are built without following the earthquake codes. Detailing that often ignored is stirrup hooks are not made with seismic hooks (135 ÌŠ), which affects confinement in the event of an earthquake. This study compares the performance of existing school buildings with detailing and without detailing (confined and unconfined) using pushover analysis for BSE-1E and BSE-2E earthquakes. The results obtained for school structures with column and beam detailing still meet the performance targets for both BSE-1E and BSE-2E earthquakes (IO and LS). While buildings that do not use detailing on their columns and beams for the BSE-1E earthquake still meet the performance target (LS), but do not meet for the BSE-2E earthquake where the performance passes Collapse Prevention (CP).